Self Management Pasien Pasca Stroke Di RSKD Dadi Provinsi Sulawesi Selatan - Sriwahyuni, Sriwahyuni (Universitas Muhammadiyah Surabaya, 2020)
Objective : Stroke is an acute neurological deficit disease caused by brain blood vessel disordes that occur suddenly, damage to brain cells after a stroke causes disability in cognitive, sensory and motor functions .Methods : This research method uses descriptive analytic type with cross sectional study design. Sampling using simple random sampling technique, obtained 59 respondents. Data collection was performed using a questionnaire and analyzed with the chi square test (p>0.05)Results : Bivariate analysisÂ results showed a self management of patients after stroke (p=0.003), which means less than (Î± < 0.05).Conclusion : Self-management in post-stroke patients in Dadi District Hospital South Sulawesi Province is not good